The T-Stems in Soqotri : A Contribution to Semitic Detransitivising Derivation - Bulakh, Maria (Language and Linguistics E-Books Online, Collection 2025., 2024)
This book presents the results of a field research on the verbal system of Soqotri, a little-studied language spoken on the island of Soqotra (Arabian Sea) and belonging to the Modern South Arabian branch of Semitic. The investigation focuses on